2015
DOI: 10.1007/s00784-015-1455-y
|View full text |Cite
|
Sign up to set email alerts
|

Three- to nine-year survival estimates and fracture mechanisms of zirconia- and alumina-based restorations using standardized criteria to distinguish the severity of ceramic fractures

Abstract: Objectives The aims of this study were set as follows:1. To provide verifiable criteria to categorize the ceramic fractures into non-critical (i.e., amenable to polishing) or critical (i.e., in need of replacement) 2. To establish the corresponding survival rates for alumina and zirconia restorations 3. To establish the mechanism of fracture using fractography Materials and methods Fifty-eight patients restored with 115 alumina-/zirconia-based crowns and 26 zirconia-based fixed dental prostheses (FDPs) were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 37 publications
1
19
0
1
Order By: Relevance
“…The annual incidence of complications for ceramic chipping has been estimated to be 0.64%; loss of another 0.64% of the crowns per year because of ceramic fractures was also estimated . Apart from inherent flaws as origins of ceramic failure, zones of occlusal contact wear have been identified as primary starting points of chipping fracture . Posterior crowns were, accordingly, found to be particularly vulnerable to chipping .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The annual incidence of complications for ceramic chipping has been estimated to be 0.64%; loss of another 0.64% of the crowns per year because of ceramic fractures was also estimated . Apart from inherent flaws as origins of ceramic failure, zones of occlusal contact wear have been identified as primary starting points of chipping fracture . Posterior crowns were, accordingly, found to be particularly vulnerable to chipping .…”
Section: Discussionmentioning
confidence: 96%
“…2 Apart from inherent flaws as origins of ceramic failure, zones of occlusal contact wear have been identified as primary starting points of chipping fracture. 16 Posterior crowns were, accordingly, found to be particularly vulnerable to chipping. 17 Rinke and colleagues confirmed this; they evaluated 323 single crowns (96 incisors, 89 premolars, and 138 molars) over a mean period of 79.7 6 14.2 months and found that placing a crown on a molar doubled the risk of chipping (hazard ratio 2.15, p 5 0.034).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Moraguez et al classified the chipping of the veneering ceramic on zirconia and alumina into critical and non-critical. A critical fracture was defined as an irretrievable loss of morphology whereas non-critical meant a fracture that did not compromise esthetics or function [62]. For single-unit crowns, the Kaplan-Meier survival estimates for critical fractures (all veneering ceramic failures) were 89.4% for an observation time of 6.3 years (mean 3.88 years).…”
Section: Clinical Findings On Veneered Zirconia Restorationsmentioning
confidence: 99%
“…The application of fractographic analysis to determine the fracture origins of crowns that have failed in service has been reported in numerous publications (Kelly et al 1990; Thompson et al 1994;Quinn et al 2005;Øilo and Gjerdet 2013;Moráguez et al 2015;Øilo and Quinn 2016). These analyses identified a number of fatigue fracture modes and the mechanisms that lead to these failures are well summarized (Zhang et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These analyses identified a number of fatigue fracture modes and the mechanisms that lead to these failures are well summarized (Zhang et al 2013). Fractures of the outer porcelain layer resulting from contact fatigue with opposing teeth have been observed in some failed crown specimens (Moráguez et al 2015;Sailer et al 2015). The application of monolithic ceramic structures reduces or eliminates the potential for failures associated with porcelain layering.…”
Section: Introductionmentioning
confidence: 99%